(untitled) (American International Journal of Business and Management Studies, 2024)
The hotel industry faces challenges related to manual management processes, which can lead to inefficiencies and errors in operations such as booking, payment processing, and administrative tasks. To address these challenges, there is a growing demand for automated systems to streamline operations and improve overall efficiency. This study investigates the design and implementation of a Python-based Hotel Management System built using the Django framework and MySQL database. The system is developed to handle essential hotel operations, including room booking, payment processing, and general management, while ensuring scalability, security, and usability. The research follows a software development approach based on functional and non-functional requirements, with a focus on unit, integration, functional, and security testing to ensure the system’s reliability and performance. Key features of the system include real-time booking functionality, secure payment processing, and authenticated user access for administrators and customers. The results reveal that the system effectively reduces operational errors, enhances the user experience for both hotel administrators and guests, and improves overall operational efficiency. The system also supports secure financial transactions and simplifies hotel management tasks through an intuitive interface. The findings suggest that the Python-based Hotel Management System provides an effective solution for automating hotel operations. It offers a scalable, secure, and user-friendly platform, optimizing both management and customer-facing tasks while improving the overall efficiency and effectiveness of hotel operations. JEL Classification Codes: O14.